Los ensayos político-culturales de Emilia Prieto Tugores (1932-1974) - Flores González, Mercedes (2013)
The author of this article makes an approach to the political-cultural discussion held by Emilia Prieto Tugores in her essays, published during the decades from 1930 to 1970 in national journals and newspapers. The aim is to recognize both the critical point of view and the revolutionary political activity in her writings, begun before Costa Rican women get the right to vote. This article is part of a research in process about Prieto’s essay works.